Species Module in Assortative Mating in Man - Wolański, Napoleon; Siniarska, Anna (Anthropological Review, 1983)
On grounds of own data as well as that taken from the literature the authors have analysed relation between assortative mating with respect to body height and population size. It has been found that in small populations (400–500 persons) usually negative assortative mating in body height occurs, while in larger populations assortative mating is positive. The authors advance a hypothesis that there exists a species-specific module of similarity between spouses. In situations when random mating is likely to lead to inbreeding (too high similarity between mates) the negative assortative mating oceurs. In situations when random mating is likely to result in too small similarity of mates (too much genetic difference between mates) the positive assortative mating occurs. The critical value of population size seems to be 500 individuals. In populations of this size there is no assortative mating. The exact critical population size depends on heterogeneity of a population and degree of its isolation.